The application of big data in the management of healthcare organizations. A review of selected practical solutions - Chluski, Andrzej; Ziora, Leszek (Business Informatics, 2015)
The goal of the paper is to present the application of big data solutions in the process of organizations’ management especially concerning healthcare subjects. It raises the issue of big data application in multiple areas, including supporting decisions and the improvement of efficiency and efficacy of the whole decision-making process. Big data technologies have manifold advantages for the organizations which implemented it and may be an element which can contribute to the achievement of a competitive advantage of such an organization. The review paper presents the notion of big data solutions with a brief presentation of its architecture and also puts an emphasis on the benefits of its application in healthcare subjects and the management of organizations. It describes the methods and techniques of data processing for the purpose of huge volumes of data analysis. On the basis of the literature review and an analysis of the McKinsey report, the Big Data Executive Survey 2013 report, IBM, Intel research and case studies, it presents selected examples of big data application in healthcare
Informatyka Ekonomiczna = Business Informatics, 2015, Nr 1 (35), s. 9-18
Keywords: Big Data; business analytics; data mining; Business Intelligence; healthcare organizations; analityka biznesowa; eksploracja danych; inteligencja biznesowa